2020
DOI: 10.1002/gepi.22357
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive genetic and epidemiological association analysis of vitamin D with common diseases/traits in the UK Biobank

Abstract: Vitamin D has been intensively studied for its association with human health, but the scope of such association and the causal role of vitamin D remain controversial. We aim to comprehensively investigate the links between vitamin D and human health through both epidemiological and Mendelian randomization (MR) analyses. We examined the epidemiological associations between serum 25‐hydroxyvitamin D (25(OH)D) concentration and 90 diseases/traits in 326,409 UK Biobank (UKBB) Europeans. The causal relations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
2
23
2
Order By: Relevance
“…386 406 participants from the four studies were included in genetic analyses (table), including 33 546 people who had coronary heart disease, 18 166 people who had a stroke, and 27 885 people who died, and 500 962 participants were included in observational analyses (appendix pp [12][13][14] . This genetic risk score was not associated with a range of cardiovascular risk factors in UK Biobank, except for BMI and HDL cholesterol, although these associations were small (appendix p 26).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…386 406 participants from the four studies were included in genetic analyses (table), including 33 546 people who had coronary heart disease, 18 166 people who had a stroke, and 27 885 people who died, and 500 962 participants were included in observational analyses (appendix pp [12][13][14] . This genetic risk score was not associated with a range of cardiovascular risk factors in UK Biobank, except for BMI and HDL cholesterol, although these associations were small (appendix p 26).…”
Section: Resultsmentioning
confidence: 99%
“…13 Null findings have been observed for several further outcomes, including other cardiovascular diseases and cancers. 14 Previous Mendelian randomisation analyses assumed a linear dose-response relationship between genetically predicted 25(OH)D and cardiovascular disease. However, some observational analyses have reported nonlinear associations, 15,16 suggesting methods that assume linearity might not provide an accurate picture of the dose-response relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, an MR study by Ye et al. ( 46 ) using 104 SNPs on women of European descent showed that higher circulating vitamin D concentrations can reduce the risk of OC. The latest study by Ong and co-workers in the face of horizontal pleiotropy involving analysis with 74 SNPs further validated this result.…”
Section: Application Of Mr In Ocmentioning
confidence: 99%
“…1,2 Observational data implicating vitamin D deficiency in CRC etiology or survival are limited by potential bias as environmental risk factors associated with CRC are also associated with vitamin D status (i.e., co-causality; e.g., physical activity), while the colorectal cancer or its treatment may impair vitamin D status (i.e., reverse causation). Indeed, a definitive causal relationship remains unproven, 3 with existing mendelian randomization (MR) studies hampered by weak genetic instrumental variables [3][4][5] and large trials (e.g., VITAL Trial 6 and ViDA study 7 ) failing to demonstrate an effect of vitamin D supplementation on CRC risk. However, a recent randomized-control trial (RCT) reported an association between supplementation, vitamin D receptor genotype and risk of colorectal adenoma, supporting the premise that the beneficial effect may be causal.…”
Section: Introductionmentioning
confidence: 99%